2021
DOI: 10.1186/s13019-021-01471-5
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical stretching of the pulmonary vein mediates pulmonary hypertension due to left heart disease by regulating SAC/MAPK pathway and the expression of IL-6 and TNF-α

Abstract: Background This study aimed to explore whether the mechanical stretching-induced expression of interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in pulmonary veins occurred through the stretch-activated channel (SAC)/ mitogen-activated protein kinases (MAPKs) pathway. Methods Sixty male Sprague-Dawley rats were divided into three sham groups and seven model groups. A metal clip was placed on the ascending aorta in the model group to establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…32 In 2009, this research team used this rat model to study PH-LHD and found that inhaled nitric oxide improved pulmonary hemodynamics and pulmonary edema in group 2 PH. 33 This animal model was further promoted, and aortic banding in rats is at present the most commonly used animal model to study PH-LHD, [34][35][36][37][38][39][40][41][42] although the timing of the banding varies depending on the operator's experience. 1.…”
Section: Aortic Banding (Aob)mentioning
confidence: 99%
“…32 In 2009, this research team used this rat model to study PH-LHD and found that inhaled nitric oxide improved pulmonary hemodynamics and pulmonary edema in group 2 PH. 33 This animal model was further promoted, and aortic banding in rats is at present the most commonly used animal model to study PH-LHD, [34][35][36][37][38][39][40][41][42] although the timing of the banding varies depending on the operator's experience. 1.…”
Section: Aortic Banding (Aob)mentioning
confidence: 99%
“…Among these, IL-6 and TNF were found to be increased in plasma, lung, pulmonary arteries and veins, as well as in PA ECs in both patients and animal models of various PH groups ( Table 1 ). In PAH patients ( 60 ) and in PH-LHD rat models ( 61 , 81 ), IL-6 contributes to PA remodeling by inducing medial wall thickening via SMC proliferation and muscularization of the distal pulmonary arterial tree due to migration of SMCs into precapillary arterioles ( 60 , 61 , 81 ) ( Table 2 ; Figure 2 ), potentially affecting arterial compliance by increased wall thickening. In the pulmonary adventitia, fibroblasts activate recruited macrophages through paracrine IL-6 signaling, initiating a pro-inflammatory and pro-fibrotic phenotype that is associated with an increased inflammatory response and vascular remodeling in PH ( 7 ).…”
Section: Inflammation-induced Arterial Wall Thickening and Ecm Remode...mentioning
confidence: 99%
“…Of relevance, these alterations in biomechanical forces acting upon the lung vascular wall can induce pro-inflammatory responses in ECs of distal PAs ( 58 , 59 ) and promote the aggregation of immune cells ( 58 ). This includes inflammatory cell recruitment and release of immune-cell-derived cytokines, such as IL-6 ( 60 , 61 ) and TNF ( 62 ) and bioactive enzymes, including MMPs ( 46 ), which may, in turn, promote vascular remodeling and stiffening processes, thus establishing a progressive vicious cycle. Such interplay between inflammation-triggered signaling events that, in turn, initiate wound healing processes and ECM remodeling, ultimately culminating in tissue fibrosis and scar formation, is well established in cardiac and systemic vascular diseases ( 63 65 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, animal models of left-sided pressure overload lead to an increase in lung inflammation and right heart hypertrophy, which can be attenuated by the administration of antibodies against interleukin-1β [12]. In similar models where the pulmonary vein is mechanically stretched, there is a demonstrable upregulation of pro-inflammatory cytokines, such as interleukin-6 and tumor necrosis factor-α [13].…”
Section: Pathogenesismentioning
confidence: 99%